Advanced organic chemistry. Part B: Reactions and Synthesis. (5th ed.) - Carey, Francis A.,1937- ; Sundberg, Richard J.,1938- (Springer, 2020)
The two-part fifth edition has been substantially revised and reorganized for greater clarity. Among the changes: Updated material reflecting advances in the field since 2001’s Fourth Edition, especially in computational chemistry; A companion Web site provides digital models for study of structure, reaction and selectivity; Solutions to the exercises provided to instructors online. The control of reactivity to achieve specific syntheses is one of the overarching goals of organic chemistry. Part B describes the most general and useful synthetic reactions, organized on the basis of reaction type. Together with Part A: Structure and Mechanisms, the two volumes are intended to provide the advanced undergraduate or beginning graduate student in chemistry with a sufficient foundation to comprehend and use the research literature in organic chemistry.